A new method for endoscopic closure of gastrocolonic fistula: novel application of a cardiac septal defect closure device (with video) - Melmed, Gil Y.; Kar, Saibel; Geft, Ivor; Lo, Simon K. (Gastrointestinal endoscopy, 2009)
Gastrocolonic fistula after percutaneous endoscopic gastrostomy PEG tube placement is an uncommon but serious complication. These fistulous tracts are often fibrotic and frequently require surgical intervention. To describe a novel endoscopic treatment for gastrocolonic fistula. Case report. Inpatient hospital setting. An 82-year-old woman was seen 1 year after PEG placement with feculent vomiting; imaging studies showed a gastrocolonic fistula. Cardiopulmonary comorbidities posed an unacceptable surgical risk. Endoscopic attempts at fistula closure with hemoclip placement and biodegradable plug were unsuccessful. Total parenteral nutrition resulted in multiple metabolic and infectious complications. Gastrocolonic fistula closure was performed twice by using cardiac septal defect closure devices. The first closure was achieved by using the Amplatzer double-disk nitinol wire mesh atrial septal defect closure device, which was deployed under endoscopic and fluoroscopic guidance across the fistula tract. The proximal disk was then injected with cyanoacrylate glue to create a watertight seal. The second closure, performed 4 months later after collapse of the initial device, was performed by using the CardioSEAL septal repair implant. This was secured in place with hemoclips and similarly injected with cyanoacrylate glue to create a watertight seal. Fistula closure, as determined by contrast gastrogram through a PEG tube and gastrograffin enema. Successful fistula closure was achieved for 4 months after initial device placement. After the second device was placed, the patient remained clinically well until her demise 18 months later from unrelated causes. These procedures were performed on only one subject. Successful endoscopic closure of gastrocolonic fistula can be achieved, even with long-standing, fibrotic fistulous tracts by using a novel endoscopic approach.